The Performance of Sepsis-3 Criteria to Predict Mortality Among Patients With Hematologic Malignancy and Post-transplant who Have Suspected Infection. (18th October 2021) - Henig, Oryan; Putler, Rosemary K B; Albin, Owen; Patel, Twisha S; Kaul, Daniel; Rao, Krishna; Kaye, Keith S
Abstract: Background: Sepsis is a leading cause of death, particularly in immunocompromised people. The revised definition of sepsis (Sepsis-3) uses the Sequential Organ Failure Assessment (SOFA) and quick SOFA (qSOFA) to identify patients with sepsis. The aim of this study was to evaluate the performance of SOFA, qSOFA, and systemic inflammatory response syndrome (SIRS) in immunocompromised patients. Methods: Adult immunocompromised patients admitted to Michigan Medicine between 2012 and 2018 with suspected infection were included based on criteria adopted from the Sepsis-3 study. Each clinical score (SOFA ≥2, qSOFA ≥2, SIRS ≥2) was added to the baseline risk model as an ordinal variable as well as a dichotomous variable, and area under the receiver operating characteristic curve (AUROC) values were calculated. In addition, breakpoints of SOFA between 2 and 10 were assessed to identify the breakpoints with the highest sensitivity and specificity for hospital mortality. The analysis was stratified for intensive care unit (ICU) status. Results: Of 2822 immunocompromised patients with a mean age of 56.8±15.6 years, 213 (7.5%) died during hospitalization. When added to the baseline risk model, SOFA score had the greatest predictive validity for hospital mortality (AUROC, 0.802; 95% CI, 0.771–0.832), followed by qSOFA (AUROC, 0.783; 95% CI, 0.754–0.812) and SIRS (AUROC, 0.741; 95% CI, 0.708–0.774). Among the SOFA breakpoints that were evaluated, SOFA ≥6 had the greatest predictive validity and a moderate positive likelihood ratio (2.75) for hospital mortality. Conclusions: The predictive validity for hospital mortality of qSOFA was similar among immunocompromised patients as that reported in the Sepsis-3 study. The sensitivity of qSOFA ≥2 for hospital mortality was low. SOFA ≥6 might be an effective tool to identify immunocompromised patients with suspected infection at high risk for clinical deterioration.